The Usage of Analytical Procedures by Yemeni Auditors: A Descriptive Analysis - Ba-Abbad, Mohammed Abobaker Mohammed (2010)
This study sets out to investigate the extent to which Yemeni auditors use analytical review procedures through different audit firms' size. It also examines the stage of auditing procedure in which analytical review procedures are implemented by Yemeni auditors. Moreover, the study determines the relationships between the importance's factors and the use of analytical review procedures. The findings of the study have indicated that the analytical procedures were utilized on high percentage by audits in large and high experienced audit firms compared to small and low experienced audit firms where the results have shown low percentage. Nevertheless, the role of auditors' perception towards analytical procedures has proved to have a significant effect of usage of analytical procedures.